An experimental study on the effects of lighting in the offices - Pekin, Sefika Ayse Nur; Unver, Fatma Rengin (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2024)
In recent years, the number of studies on light and its effects on human beings has increased significantly. Various studies have shown that light has non-visual as well as visual effects on humans, and that these effects direct physiological, psychological, and behavioral responses such as alertness and circadian rhythms. The relevant literature cites national/international standards, legislation, metric/numerical measurement methods, and some suggested calculation methods (Circadian Stimulus, Equivalent Melanopic Lux, etc.) to quantify these effects. However, the data on the measuring instruments used and the measurement methods followed in indoor/in situ studies are quite limited. In order to contribute to the subject, research has been initiated to determine the visual and non-visual effects of light on indoor working environment users. This research presents and compares the results of an experimental study carried out to compare the photometric and radiometric measurement results of the same parameters (Ev, EML, Tcp values) by two different devices. To this end, measurements were taken in two different office environments with different daylight proportions to assess whether and under which conditions the devices could be used as substitutes for one another. In order to achieve this, hypothesis tests were applied to the test results to estimate the probability of the two measurements being equal.
Keywords: Colour temperature; equivalent melanopic lux; illuminance; office; non visual effects of light; photometer; spektroadiometer; ACTION SPECTRUM; Architecture